Figure 4 from: Shandikov G, Eakin R (2013) Pogonophryne neyelovi, a new species of Antarctic short-barbeled plunderfish (Perciformes, Notothenioidei, Artedidraconidae) from the deep Ross Sea. ZooKeys 296: 59-77. https://doi.org/10.3897/zookeys.296.4295 - Shandikov, Gennadiy; Eakin, Richard (Zenodo, 2013)
Figure 4 - Pogonophryne neyelovi sp. n., freshly caught specimen (not preserved), 305 mm TL, 253 mm SL: a lateral view b dorsal view c ventral view d mental barbel (dorsolateral view). Scale bars 10 mm. Photo by Yu. Korzun. Scale bars 10 mm.